1999
DOI: 10.1159/000054398
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal and Age-Related Influences on NMDA-Induced Growth Hormone Secretion in Male Rats

Abstract: Activation of N-methyl-D,L-aspartic acid (NMDA) receptors stimulates growth hormone (GH) secretion. The mechanisms involved in this action are still a matter of debate. Present experiments were carried out to assess specifically: (1) the age-related changes in NMDA effects; (2) the physiological role of NMDA in pulsatile GH secretion; (3) the hypothalamic and/or pituitary actions of NMDA, and (4) the influence of gonadal function on NMDA-induced GH release. NMDA (15 mg/kg i.p.) stimulated GH secretion in neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(44 reference statements)
3
9
0
Order By: Relevance
“…The fast neurotransmitters GABA and glutamate were implicated previously in controlling GH secretion (Giustina and Veldhuis, 1998;Gonzalez et al, 1999;Müller et al, 1999;Pinilla et al, 1999), and we can now confirm that they regulate GHRH neurons directly, in a monosynaptic manner. Furthermore, disabling action potential propagation with TTX blunted of the effects of these neurotransmitters on GHRH neurons in vitro.…”
Section: Intrinsic Properties Of Ghrh-gfp Neuronssupporting
confidence: 78%
See 1 more Smart Citation
“…The fast neurotransmitters GABA and glutamate were implicated previously in controlling GH secretion (Giustina and Veldhuis, 1998;Gonzalez et al, 1999;Müller et al, 1999;Pinilla et al, 1999), and we can now confirm that they regulate GHRH neurons directly, in a monosynaptic manner. Furthermore, disabling action potential propagation with TTX blunted of the effects of these neurotransmitters on GHRH neurons in vitro.…”
Section: Intrinsic Properties Of Ghrh-gfp Neuronssupporting
confidence: 78%
“…Furthermore, GABAergic and glutamatergic inputs to the GHRH system, implicated indirectly from effects on GH release, have not yet been studied directly at the hypothalamic GHRH level (Giustina and Veldhuis, 1998;Gonzalez et al, 1999;Müller et al, 1999;Pinilla et al, 1999). How these transmitters regulate GHRH neurons is of considerable interest, because data related to feeding circuits showed that GABAergic and glutamatergic neurons play a central role in the organization of arcuate nucleus activity (Horvath and Diano, 2004;Sternson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal rats, GH secretion is stimulated by γ-aminobutyric acid (GABA) [3], thyrotropin-releasing hormone (TRH) [4, 5], growth-hormone-releasing hormone (GHRH) [6]and excitatory amino acids (EAAs) [7]. The stimulatory effect of EAAs is mediated by activation of N-methyl- D -aspartate (NMDA), kainate and (±)-α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…To carry out the proposed analysis, 5-day-old rats were used, a model selected on the basis of previous reports showing the ability of GABA, NMDA, and AMPA to stimulate GH secretion during the neonatal period, in particular at that age [3, 8, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the drugs were dissolved in saline up to the working concentration. The doses and route of administration of different drugs as well as the time-points for hormone measurements were selected based on the previously reported effectiveness (Negro-Vilar et al 1979, Martin et al 1995, Pinilla et al 1998, Gonzalez et al 1999a and the absence of behavioural changes. In addition, to analyse the effectiveness of AMPA to change PRL secretion after blockade of different receptor subtypes as well and in hyper-and hypo-prolactinaemic situations, NBQX, MK-801, -MPT, DDC, 5-HTP and fluoxetine were injected prior to AMPA administration.…”
Section: Animals and Drugsmentioning
confidence: 99%